Etnopedagogi Berbasis Nilai-Nilai Hindu Kaharingan dalam Pembelajaran Pendidikan Agama Hindu di Sekolah Dasar : Etnopedagogi Berbasis Nilai-Nilai Hindu Kaharingan dalam Pembelajaran Pendidikan Agama Hindu di Sekolah Dasar - yhani, putu; Purnamiasih, Ni Wayan; Tia Ariani, Ni Kadek; Agustina, Leli (Guna Widya: Jurnal Pendidikan Hindu, 2026)
The ethnopedagogical approach positions local wisdom as a contextual and meaningful learning resource within the educational process. In the context of Hindu Religious Education in Central Kalimantan, the values of Hindu Kaharingan as a system of religiosity and local wisdom of the Dayak community possess significant potential to be integrated into learning at the elementary school level. However, studies discussing the integration of Hindu Kaharingan values into Hindu Religious Education learning remain limited and have not yet been formulated conceptually and systematically. This article aims to analyze and formulate a conceptual framework for the integration of Hindu Kaharingan ethnopedagogy in Hindu Religious Education learning in elementary schools. This study employs a qualitative approach using a library research method through the examination of scholarly books, journal articles, and relevant educational policy documents. Data analysis was conducted using content analysis techniques. The findings indicate that Hindu Kaharingan values which encompass spiritual, cosmological, social, and moral dimensions have strong relevance to the objectives of Hindu Religious Education, particularly in fostering sraddha and bhakti, ecological awareness, and students’ social character. The novelty of this article lies in the formulation of Hindu Kaharingan ethnopedagogy as a conceptual foundation for Hindu Religious Education learning in elementary schools rooted in the religious locality of the Indonesian archipelago. Therefore, Hindu Kaharingan–based ethnopedagogy can serve as a theoretical foundation for the development of contextual and meaningful Hindu Religious Education learning. Keywords: ethnopedagogy, Hindu Kaharingan, local wisdom, Hindu Religious Education, elementary school